Agroecology: from necessity to option. The case of the the vegetable gardens of Valle Viejo, Catamarca (Huellas, 2024)
This paper shares the first reflections of an agroecology experience carried out by women -rural and urban- from the department of Valle Viejo, Catamarca, who became food producers in the context of the pandemic. The turning point was the arrival of the Rural Women Program in 2020, through which many women joined it, learning how to work the land and new paradigms linked to agroecology; firstly, out of necessity, then as a possible option. As social researchers, we are interested in analyzing that particular spatial and historical experience that does not admit copying from another. In this case, women force us  to enrich existing theoretical corpus on agroecology from a situated experience that has little to do with what has already been written. Finally, the contribution that we will share comes from an ongoing research, and it is intended to show the multifactoriality of the space that occupies us, the dialogues emerged and the possibilities of carrying out a collaborative work in the production of new knowledge.